Teachers' Attitudes Toward Bullying and Intervention Responses: A Systematic and Meta-analytic Review - Dawes, Molly; Malamut, Sarah T.; Guess, Hannah; Lohrbach, Emily (SPRINGER/PLENUM PUBLISHERS, 2025)
Teachers are key to antibullying efforts, and their attitudes toward bullying can influence their intervention responses. There has been a proliferation of this type of research but thus far no review has been performed to coalesce the evidence. Following PRISMA and Cochrane guidelines, we performed a systematic and meta-analytic review. A total of 3990 titles and abstracts identified across 7 databases (PsycINFO, Education Source, ERIC via EBSCOhost, ERIC via ProQuest, Web of Science, ProQuest Dissertations and Theses, Google Scholar) were screened against inclusion and exclusion criteria. After screening, 27 studies were included in the systematic review, 25 of which were included in meta-analyses. The association between antibullying attitudes and intervention responses differed depending on whether (1) measures assessed retrospective reports of intervention responses (i.e., how often teachers used that response) versus intervention intentions (i.e., likelihood they would intervene in hypothetical scenarios) and (2) the specific type of intervention response. Results indicate that teachers' antibullying attitudes were positively related to some responses (disciplining/punishing bullying, victim support, involving parents, involving peer bystanders), negatively related to some responses (advocating avoidance, encouraging independent coping), and unrelated to others (advocating assertion, enlisting other adults, separating students). Results also indicate a positive overall association between antibullying attitudes and intervention likelihood. No moderation by form of bullying was found. Implications for preservice training and in-service teachers' professional development to target bullying attitudes are discussed.